COMPOSITION UNIQUENESS OF “KONARMIA” (“CAVALRY ARMY”) BY I. BABEL - Feliks M. Shteinbuk (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The interest to literary works of I. Babel has not decreased for the last few years. However, the problem of the author’s main book is not solved yet because the history of writing “Konarmiya” (“Cavalry Army”) proves that the initial discrete character of the composition turns the standard situation which leads to formation of the unique genre of Babel’s book. The aim of the article is to analyze the plot composition of “Konarmiya” (“Cavalry Army”) and define the character of its composition uniqueness and genre of this literary work, applying the comparative approach and using elements of the hermeneutic method, and also structural and functional methods. The episodes, included in the best book of the writer, were initially published as separate stories and novellas in varied newspapers and magazines mostly in 1923-1924. If we make a comparative analysis of the episodes sequence, taking into account the date when they were published and the configuration done by the writer in the final variant, it will become obvious that the order of publishing does not correspond to either the dates, or their order in the traditional variant of some editions of “Konarmiya” (“Cavalry Army”). The discrepancy of the episodes sequence according to every position can indicate that their final configuration is the result of not a random but a conscientious choice based on the specific composition design. The examples to testify the aforementioned view on the creation of “Konarmiya” (“Cavalry Army”) can be the following episodes, such as “A Letter”, “Crossing the Zbruch”, “The Church at Novograd” or “Betrayal”, “Argamak”, “A Kiss” because their position in the book is strictly determined and not accidental. Another example of how important the composition structure of “Konarmiya” (“Cavalry Army”) for its content is the presence and position of the episodes related with the topos of movement. There are a few episodes in the book, namely “Crossing the Zbruch”, “The Chief of Konzapas”, “The Road to Brody”, “Discourse on the Tachanka”, “The Story of a Horse”, “Konkin”, “The Story of a Horse, Continued”, “Argamak”. Thus, having analyzed the composition uniqueness of “Konarmiya” (“Cavalry Army”), we can state that first, the book by I. Babel is the result of long, controversial, stressed, and often painful search of the appropriate form to depict the artistic idea which is the basis of this literary work. Second, the composition of “Konarmiya” (“Cavalry Army”) is not an arbitrary or random selection of works but a thoroughly built and tightly bound structure, every part of which, becoming a part of the whole, almost loses its “independence” and “autonomy” because it is determined and in its turn determines other parts of the book. Finally, third, the discrete, interrupted character of the composition of “Konarmiya” (“Cavalry Army”) does not deny that this literary work is integral but only indicates a different way to organize artistic space, a novel one in particular, and establishes the possibility of divergent form of the novel or a «discrete» novel. It is such a genre variety which is based on the principle of interrupted continuity and negation of linear development of events while depicting the characters and building the text composition.